CHANGES OF PLANT COMMUNITIES AND SOIL PROPERTIES DUE TO DEGRADATION OF ALPINE WETLANDS ON THE QINGHAI-TIBETAN PLATEAU - Gao, Y. H.; Schumann, M.; Zeng, X. Y.; Chen, H. (2011)
Changes of plant communities and soil properties within alpine wetlands on the Qinghai-Tibetan plateau due to degradation were investigated. Biotic and abiotic site parameters were tested to assess site characteristics of degraded and undegraded wetland sites. It is shown that vegetation coverage, above- and below-ground biomass was significantly lower within degraded alpine wetlands than within undegraded sites. The appearance of plant communities as well as the emergence of specific species were identified as tool to assess wetland degradation. Kobresia tibetica dominates undegraded sites but is withdrawing with advancing degradation, due to an increasing establishment of annual or biennial forbs. Wetland degradation also seems to be indicated by the development from marsh to xerophytic vegetation. The amounts of soil bacteria and fungi were higher in degraded than in undegraded sites. No significant differences of enzyme activities were observed between degraded and undegraded sites. The content of clay and water was lower in soil samples of degraded than of undegraded sites. Soil organic carbon, total N and available N were significantly lower within degraded sites.